2016
DOI: 10.1037/dev0000073
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitivity to audiovisual temporal asynchrony during midchildhood.

Abstract: Temporal proximity is one of the key factors determining whether events in different modalities are integrated into a unified percept. Sensitivity to audiovisual temporal asynchrony has been studied in adults in great detail. However, how such sensitivity matures during childhood is poorly understood. We examined perception of audiovisual temporal asynchrony in 7-8-year-olds, 10-11-year-olds, and adults by using a simultaneity judgment task (SJT). Additionally, we evaluated whether non-verbal intelligence, ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…The ability to detect multisensory temporal asynchrony has a prolonged developmental course, with even adolescents still performing worse than adults (Hillock-Dunn & Wallace, 2012). More importantly, perception of AV asynchrony matures before that of VA asynchrony, with 10-11 children significantly outperforming their 7-8 year old peers on a SJT, but only at AV SOAs (Kaganovich, 2016). Further, several studies have demonstrated that the size of the TBW is malleable and can be reduced through perceptual training (Powers III et al, 2012; Powers III et al, 2009; Stevenson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to detect multisensory temporal asynchrony has a prolonged developmental course, with even adolescents still performing worse than adults (Hillock-Dunn & Wallace, 2012). More importantly, perception of AV asynchrony matures before that of VA asynchrony, with 10-11 children significantly outperforming their 7-8 year old peers on a SJT, but only at AV SOAs (Kaganovich, 2016). Further, several studies have demonstrated that the size of the TBW is malleable and can be reduced through perceptual training (Powers III et al, 2012; Powers III et al, 2009; Stevenson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The stimuli and design of this study were identical to those described in two previous publications from our laboratory (Kaganovich, 2016; Kaganovich et al, 2014). A 2 kHz pure tone and a flash of light (shaped as a cartoon explosion, see Figure 1) served as stimuli.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Audiovisual temporal acuity normally undergoes fine-tuning throughout childhood and adolescence (Hillock et al, 2011 ; Hillock-Dunn and Wallace, 2012 ; Lewkowicz and Flom, 2014 ; Kaganovich, 2016 ), making this perceptual ability susceptible to disruption in individuals with developmental disabilities, such as autism spectrum disorder (Bebko et al, 2006 ; Foss-Feig et al, 2010 ; Kwakye et al, 2011 ; de Boer-Schellekens et al, 2013 ; Stevenson et al, 2014a , b ), dyslexia (Hairston et al, 2005 ; Wallace and Stevenson, 2014 ) and schizophrenia (Foucher et al, 2007 ; Carroll et al, 2008 ; Martin et al, 2013 ; Stekelenburg et al, 2013 ; Haß et al, 2017 ; Stevenson et al, 2017 ). In such cases, atypical audiovisual temporal acuity often manifests as an increased length of time over which audiovisual stimuli are perceptually bound (i.e., the TBW is wider).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, unitization of intersensory information provides a meaningful basis for perception, learning, and memory (Bahrick & Lickliter, 2012). These skills emerge in infancy and are refined across childhood (Bahrick, 2010; Bahrick & Lickliter, 2002; Kaganovich, 2016; Lewkowicz, 2000, 2014). …”
mentioning
confidence: 99%